World development report 2011 : conflict, security, and development - World Bank. (Washington, DC : World Bank, 2011)
The 2011 World Development report looks into the changing nature of violence in the 21st century. It underlines the negative impact of persistent conflict on a country's or region's development prospets, and notes that no low-income, conflict-affected state has yet achieved a single Millennium Development Goal.
" ... a product of the staff of the International Bank for Reconstruction and Development/The World Bank."--Verso of title page.
Includes bibliographic references and index.
nif 26/04/13
Ref.
Keywords: Economic development; Conflicts; Security; Economic violence